2022
DOI: 10.3389/fmicb.2022.992660
|View full text |Cite
|
Sign up to set email alerts
|

The effects of urban land use gradients on wild bee microbiomes

Abstract: Bees and their microbes interact in complex networks in which bees form symbiotic relationships with their bacteria and fungi. Microbial composition and abundance affect bee health through nutrition, immunity, and fitness. In ever-expanding urban landscapes, land use development changes bee habitats and floral resource availability, thus altering the sources of microbes that wild bees need to establish their microbiome. Here, we implement metabarcoding of the bacterial 16S and fungal ITS regions to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 117 publications
1
7
0
Order By: Relevance
“…The diverse array of bacterial communities in Ontario included Acinetobacter and Enterobacter, but notably lacked Apilactobacillus (Figure 5A). This is consistent with patterns noted in the small carpenter bee Ceratina calcarata, where the normally ubiquitous Apilactobacillus was present in low relative abundances in Ontario (Nguyen & Rehan, 2022b), despite being previously characterised as a core bacterium and being found in almost all other bees (Graystock et al, 2017;Martinson et al, 2011;Nguyen & Rehan, 2022b, 2023aShell & Rehan, 2022). Martinson et al (2011) similarly found the absence of the bacterial phylotypes associated with the genus Lactobacillus.…”
Section: The Microbiome Across a Geographical Rangesupporting
confidence: 86%
See 2 more Smart Citations
“…The diverse array of bacterial communities in Ontario included Acinetobacter and Enterobacter, but notably lacked Apilactobacillus (Figure 5A). This is consistent with patterns noted in the small carpenter bee Ceratina calcarata, where the normally ubiquitous Apilactobacillus was present in low relative abundances in Ontario (Nguyen & Rehan, 2022b), despite being previously characterised as a core bacterium and being found in almost all other bees (Graystock et al, 2017;Martinson et al, 2011;Nguyen & Rehan, 2022b, 2023aShell & Rehan, 2022). Martinson et al (2011) similarly found the absence of the bacterial phylotypes associated with the genus Lactobacillus.…”
Section: The Microbiome Across a Geographical Rangesupporting
confidence: 86%
“…Across all samples, we did not expect any potential impact of ethanol storage or washing on microbiome composition, as Hammer et al (2015) discovered that there were limited effects of surface sterilisation on microbiome characterisations and storage in 95% ethanol when compared to other storage methods. However, Apilactobacillus are found in practically all studied bees (Kwong & Moran, 2016;Martinson et al, 2011;Nguyen & Rehan, 2023a;Shell & Rehan, 2022), playing important roles in building immunity (Daisley et al, 2017; and aiding in host learning and memory behaviour (Zhang et al, 2022). Although potentially correlated to patterns of low relative abundances of Apilactobacillus in urban Ontario (Nguyen & Rehan, 2022b) and in agreement with Martinson et al (2011), which found the absence of Firm-4 and Firm-5 bacterial phylotypes in A. virescens, considerations should be made regarding the effectiveness of certain T A B L E 1 The core microbiome of Agapostemon virescens found at a frequency of at least 1% and detected in at least 50% of the samples, across all provinces and collection methods.…”
Section: Collection Methods Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we found that overall bacterial diversity was highest in urban areas which corroborates the findings of a recent study that also found bacterial richness in C. calcarata increased as urbanization increased (Nguyen & Rehan, 2022a). The authors also found that certain core microbiota differed in their abundance depending on urbanization level, such as Apilactobacillus and Acinetobacter core bacteria overabundant in rural sites, but the fungi Penicillium , which plays a role in bee immunity (Yoder et al, 2013), was abundant in urban areas (Nguyen & Rehan, 2022b). Likewise, we also found the change in metagenomic diversity revealed interesting patterns of abundance for core microbiota, such as the core family Lactobacillaceae, which was abundant in sites with high development.…”
Section: Discussionmentioning
confidence: 99%
“…Some bee symbionts can survive at temperatures up to 52°C, whereas others are not able to grow below a certain thermal limit (29°C). On the other hand, functionally important bacteria, such as Apilactobacillus, are overrepresented in areas with lower annual temperatures (Nguyen and Rehan, 2022). Moreover, in honeybees there is a seasonal dominance of the non-core bacteria Bartonella, which is associated to dietary shifts caused by low temperatures in winter (Li et al, 2022a).…”
Section: Microorganisms Associated With Bees and The Uhi Effect 41 Sy...mentioning
confidence: 99%